Digitalization of the educational process at the university: advantages and prospects - Iskhakbayeva, T.G.; Shkutina, L.A.; Yelshina, M.K. (Karagandy University of the name of acad. E.A. Buketov, 2023)
In the article, the authors analyze the process of digitalization of the educational process at the university. The relevance of the topic is determined by the special role of the use of innovative technologies in the learning process. In the process of modernization of the education system, innovations are introduced into the educational process of universities from year to year, which in one way or another are aimed at improving the quality of education. The authors characterize the current state of digitalization of the educational process of the Republic of Kazakhstan and note the advantages of using digital technologies. In addition, the authors analyze the further prospects of the digitalization process.
Цифровизация образовательного процесса в вузе: преимущества и перспективы
Жоғары оқу орындағы білім беру процесін цифрландыру: артықшылықтары мен болашағы
Keywords: education; digitalization; innovations; digital technologies; educational process; higher educational institution